Development of a Pharmacognosy Laboratory Manual for First-Year Pharmacy Students: A Cross-Sectional Needs Assessment - Awatf Abadi; Eman Saleh; Alla Nagah (AlQalam Journal of Medical and Applied Sciences, 2026)
Pharmacognosy is a core discipline in pharmaceutical education that relies on laboratory-based learning to develop students’ skills in identifying medicinal plant materials. However, first-year pharmacy students often face challenges in understanding microscopic structures and laboratory procedures due to limited visual and structured resources. This study aimed to design a pharmacognosy laboratory manual based on the educational needs of first-year students at the University of Tripoli. A descriptive cross-sectional design was adopted, and a structured questionnaire was distributed to students enrolled in or who had completed the course. A pilot study (n=32) was conducted to assess reliability, followed by a final sample of 142 valid responses. The questionnaire covered demographics, laboratory difficulties, learning preferences, and improvement suggestions. Content validity was confirmed by academic staff review, and reliability was established using Cronbach’s alpha (0.70–0.766). Data were analysed using SPSS with descriptive statistics. Most students (90.2%) supported the need for an integrated guide linking theory with microscopic visualization and assessment. Challenges included limited access to microscopic images (50.7%) and fragmented digital resources (58.5%). Difficulties were reported in identifying calcium oxalate crystals, fibers, vessels, and trichomes. Students highly valued digital PDF resources with QR codes (97.2%) and experiment checklists (93.0%). High agreement was also observed for peer learning, botanical garden integration, and the use of Libyan medicinal plants. The findings support the development of an interactive pharmacognosy laboratory manual to enhance students’ understanding, engagement, and practical skills.